Hypothermia at Birth and its Associated Com- plications in Newborn infants: a Follow up Study - F Nayeri; F Nili (Tehran University of Medical Sciences, 2006)
Hypothermia is one of the main causes of neonatal mortality in developing countries. The aim of this prospective study was to determine the relationship between hypothermia at birth and the risk of mortality or morbidity among neonates born in Imam Hospital in Tehran, Iran. During a one-year period, body temperature was taken from all newborns using a low-reading rectal thermometer, immediately after their admission into the Neonatal ward of the above hospital. A temperature less than 36.5C was considered as hypothermia. A questionnaire was filled for each subject. Using logistic regression the risk of development of respiratory distress in the first six hours of birth, hypoglycemia, metabolic acidosis, hyperbilirubinemia, scleroderma, pulmonary hemorrhage, Disseminated Intravascular Coagulopathy (DIC) in the first three days of birth were assessed and compared with the hypothermic and normothermic newborn infants. Nine hundred and forty neonates were enrolled into the study. A significant relationship was found between hypothermia and respiratory distress in the first six hours of birth and death, as well as with jaundice, hypoglycemia and metabolic acidosis in the first three days of birth (P=0.0001). Logistic regression showed that, regardless of weight and gestational age, hypothermia at birth alone could increase the risk of neonatal death (OR=3.64, CI=1.85-7.18), Respiratory distress (OR=2.12, CI=1.53-2.93), metabolic acidosis (OR=2.83, CI=1.74-4.59) and jaundice (OR=2.01, CI=1.45-2.79). Neonatal hypothermia at birth increases mortality as well as significant morbidity and hospitalization period.